Analysis of Mathematics Learning Difficulties in Addition and Subtraction Material in Class II of SD Negeri 1 Ngumpul - Ireniza, Citra; Subayani, Nataria Wahyuning (Pedagogia : Jurnal Pendidikan, 2024)
This research aims to examine the problems faced by students when learning mathematics in class II elementary school, especially in addition and subtraction material. This research is a type of qualitative research conducted in September 2023 at SD Negeri 1 Ngumpul. The method used is descriptive, with the research subject focusing on class II students. Research instruments include the use of tests, interviews, and document collection. The analytical method used is Miles and Huberman's interactive analysis, which includes the stages of data collection, data reduction, data presentation, and drawing conclusions. Research findings indicate that 1) a number of students have difficulty understanding addition and subtraction material; 2) this difficulty is caused by limited reading ability, so students find it difficult to understand the meaning of the questions; 3) This problem is also experienced by class II students because their understanding of the concept of sequential addition and subtraction is still not optimal; 4) students' learning difficulties are caused by a lack of attention to the use of addition and subtraction symbols in saving and borrowing techniques. Based on research suggestions, it is to support assistance in the process of learning addition and subtraction by educators or parents, as well as presenting questions in stages, according to commonly used learning methods.